UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MENYIMAK TEKS BACAAN BAHASA INDONESIA KELAS 2 DAN 3 UPT SDN 21 BARRU - Fajria Salsabila; Isnadatul Muhnadiyah, Abdul Azis (STKIP Subang, 2025)
This research aims to improve the learning outcomes of grade 2 and 3 students at UPT SDN 21 Barru in listening to Indonesian reading texts through the application of innovative learning strategies. The problem identified is the low ability of students to understand the content of reading texts which is caused by a lack of variety in learning methods and less than optimal use of learning media. This research uses the classroom action research (PTK) method carried out in two cycles, where each cycle includes the stages of planning, implementation, observation and reflection. The results of the research show that there is an increase in learning outcomes as seen from the average student score which has increased in each cycle and the increase in active participation of students during the learning process.